Ricinus poisoning in a two-year-old child – case report - Kocić, Marija; Ristić, Snežana (Archives of Pharmacy, 2022)
Plant poisoning in children are the second most common, immediately after drug poisoning. Castor oil, which is grown as an ornamental plant, contains the extremely toxic chemical, ricin in the seeds. Intoxication occurs when castor seeds are chewed and swallowed, or when powder from particles of the fruit is inhaled. Toxic effects are manifested in the form of drowsiness, vomiting and profuse diarrhea, and may progress to circulatory failure. There is no specific antidote for ricin. The mortality rate, despite the applied treatment measures, is about 5%. The aim of this study was to present a 2-year-old male patient with an acute, unintentional and severe ricin poisoning. Anamnestic data indicate that boy developed gastrointestinal disorders soon after consuming castor seeds. First aid was provided before admission to our hospital. Despite the severe clinical presentation, the outcome of the treatment was favorable. Based on the presented case, it can be concluded that the severity of the clinical presentation of castor poisoning is determined by the method of poisoning, as well as the dose, i.e. the amount of substance ingested. In addition to the severity of clinical presentation, a positive treatment outcome is possible with therapeutic procedures, based on non-specific detoxification measures and supportive therapy.